The lichen family Physciaceae in Thailand—I. The genus Pyxine - Mongkolsuk, Pachara; Meesim, Sanya; Poengsungnoen, Vasun; Kalb, Klaus (Phytotaxa, 2012)
A revision of the Pyxine collections from Thailand is presented. Sixteen previously described species were found in this material and descriptions are provided for P. asiatica, P. australiensis, P. coccifera, P. cocoës, P. cognata, P. coralligera, P. cylindrica, P. daedalea, P. meissnerina, P. petricola, P. philippina, P. profallax, P. retirugella, P. schmidtii, P. sorediata and P. subcinerea. Descriptions are also included in the paper for P. berteriana and P. farinosa, because these species may well occur in Thailand. Pyxine boonpragobiana Kalb & Mongkolsuk, P. dactyloschmidtii Kalb & Mongkolsuk, P. pseudokeralensis Kalb, Mongkolsuk & Buaruang, and P. subcoralligera Kalb, Mongkolsuk & Boonpragob are described as new to science. A key for the identification of all species is provided. Terpene profiles for similar species which cannot be distinguished by spot-tests are presented and Rf-values for the most important terpenes are given. Photos showing the new species as well as characteristic structures in the genus are also provided.